Impacto de choques transitorios y de largo plazo en el PIB e Inflación de Bolivia: Un modelo de vectores autorregresivos estructurales - Ernesto Bernal Martínez (Institute for Advanced Development Studies (INESAD), 2020)
– This research aims to estimate the impact of short and long-term structural shocks on the Gross Domestic Product (GDP) as well as on prices in Bolivia. The methodology used was structural autoregressive vectors and the data used came from the National Institute of Statistics. Results shows that supply shocks impact positively on the GDP, and lead to a drop in the price level. The demand shocks on GDP and prices in Bolivia are negative. Furthermore, I find that the political, subprime and commodity crises have had a negative impact on GDP growth.
Keywords: E31; E32; 330; Growth; prices; autoregressive vectors; transitory shocks; long-terms shock